Stunting and Poverty Management Strategies in the Palembang City, Indonesia - Bachtari Alam Hidayat; Putri Erlyn (Randwick International of Social Science Journal, 2021)
Stunting that has occurred if not addressed will cause public health problems. Investments in human resources are important to improve competitiveness, and tackling stunting be a concrete step that greatly contribute to improving the quality of life of the people. The achievement of reducing stunting rates is still far from the target, so a systematic evaluation of government programs is needed. The study applies quantitative and qualitative methods to describe the conditions of stunting and poverty in Palembang City, the factors that cause poverty, analyzes opportunities, threats, strengths and weaknesses in empowering activities for the poor and formulates strategies to alleviate stunting and poverty. Strategies to accelerate stunting reduction are family food security and parenting that determine nutritional adequacy and are strengthened by coordination of poverty alleviation programs, namely the New Entrepreneurial Growth Program and empowerment of micro and small businesses. Areas near the river have water plants “enceng gondok” that can be processed into products of economic value and also as a solution for river hygiene. The government policy must also support this activity by requiring the use of water hyacinth handicraft products as a solution to reducing plastic use. In addition, there are mussels or shellfish typical of the city of Palembang and fish which can be used as innovative products for the development of typical Palembang food besides pempek and crackers. The programs designed can be implemented effectively and achieve the desired goals by socializing and maximizing the number and quality of assistants in accordance with the number of poor people who must be assisted on an ongoing basis.